Pengembangan Berbasis Budaya Untuk Keberlanjutan UKM: Industri dan Manajemen Warisan Pusaka di Indonesia dan Brunei Darussalam - Susminingsih Husien; Agus Fakhrina; Abdul Nasir bin Hj. Abdul Rani (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This paper focus on the Culture-Led Development (CLD) role on the exploration of industrial and personal heritage management that encourages the development of SMEs as it has been implemented in Indonesia and Brunei Darussalam. This qualitative research with an antrophology approach was conducted with semi-structured interviews beside the observation and documentation involving 13 SMEs entrepreneurs, who have produced traditional or handicraft items, in 2018. The empirical data was used to illustrate the implementation of culture in business development. The term heritage has been identical with the sustainability of SMEs. The CLD helps change the entrepreneurs' way of thinking as it promotes innovative products that are environmentally friendly and are able to elevate cultural values and tradition. This research finds that culture and heritage-based management have strong implications for the SMEs development.